Genotyping of Campylobacter jejuni and prediction tools of its antimicrobial resistance - Strakova, Nicol; Michova, Hana; Shagieva, Ekaterina; Ovesna, Petra; Karpiskova, Renata; Demnerova, Katerina (Folia microbiologica, 2024)
Although Campylobacter jejuni is the pathogen responsible for the most common foodborne illness, tracing of the infection source remains challenging due to its highly variable genome. Therefore, one of the aim of the study was to compare three genotyping methods (MLST, PFGE, and mP-BIT) to determine the most effective genotyping tool. C. jejuni strains were divided into 4 clusters based on strain similarity in the cgMLST dendrogram. Subsequently, the dendrograms of the 3 tested methods were compared to determine the accuracy of each method compared to the reference cgMLST method. Moreover, a cost-benefit analysis has showed that MLST had the highest inverse discrimination index (97%) and required less workflow, time, fewer consumables, and low bacterial sample quantity. PFGE was shown to be obsolete both because of its low discriminatory power and the complexity of the procedure. Similarly, mP‑BIT showed low separation results, which was compensated by its high availability. Therefore, our data showed that MLST is the optimal tool for genotyping C. jejuni. Another aim was to compare the antimicrobial resistance to ciprofloxacin, erythromycin, and tetracycline in C. jejuni strains isolated from human, water, air, food, and animal samples by two gene sequence-based prediction methods and to compare them with the actual susceptibility of C. jejuni strains using the disc diffusion method. Both tools, ResFinder and RGI, synchronously predict the antimicrobial susceptibility of C. jejuni and either can be used.
Keywords: Anti-Bacterial Agents; bakteriální léková rezistence; genotyp; kampylobakterové infekce; Drug Resistance, Bacterial; Genotype; Antimicrobial resistance; MLST; ResFinder; cgMLST; RGI; Microbial Sensitivity Tests; Multilocus Sequence Typing; zvířata; Humans; Campylobacter jejuni; antibakteriální látky; Campylobacter Infections; PFGE; multilokusová sekvenční typizace; mikrobiální testy citlivosti; mP-BIT; lidé; Animals